IMPORTANCE OF ORGANIZATIONAL CULTURE IN DIGITAL ERA - Dini Dwi Wahyuningsih; Rany Aprilliana; Ananda Nirmala; Rio Mahesa Wahyu Pratama; Wanda Riana (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
Organizational culture has an important role in supporting company performance, especially in the digital era. A strong organizational culture is able to create a unique identity, provide a code of conduct, and encourage innovation, productivity, and collaboration in the work environment. Companies that succeed in developing an adaptive and innovative work culture can effectively deal with technological developments and market dynamics, thus ensuring the company's competitiveness and sustainability. This research highlights the importance of building an adaptive work culture through the integration of digital technology and employee skill development. In addition, a culture that supports innovation provides space for employees to contribute through creative ideas and solutions that suit market needs. This is a key element for companies that want to stay relevant and achieve optimal performance in the midst of rapid change. The results of this study confirm that organizational culture is not just an operational framework, but a strategic asset that drives company growth and resilience. By building an adaptive, collaborative, and innovative culture, organizations can achieve long-term success in an increasingly complex business environment.